Taxonomic utility of old names in current fungal classification and nomenclature: Conflicts, confusion & clarifications - M. C. Dayarathne (2018)
© Guizhou Academy of Agricultural Sciences. Fungal taxonomy has a long history and nomenclatural type specimens constitute an integral part of fungal classification and nomenclature. To date, type specimens/old names have served as excellent exemplars and references and have been the pillar for a stable classification and appropriate nomenclature. However, with an increase in the number of species being discovered and the practical problems associated with re-examination and over reliance of old names as exemplars, there is a need to reconsider our traditional taxonomic thinking towards such an approach. It is becoming increasingly clear that loaning specimens, especially of rare and old species, is becoming too tedious, difficult and in some cases, practically impossible. This paper addresses in detail some of the major practical difficulties in referring to old names from a stable nomenclatural system viewpoint, in particular, reluctance of herbaria to loan specimens and poor conditions of specimens. Specific case studies where problems are encountered that hinder references to old names are discussed. Last but not least, mycologists express their opinions and concerns and provide deductive conclusions based on facts and their long experience in mycology. With regards to fungal nomenclature, taxonomists, devoted to bring about rational changes to fungal taxonomy, should be encouraged to use more friendly and practical approaches, with minimum hassle to examine old specimens. We contemplate that this paper will provide potential solutions to facilitate future naming/classification of fungal species.